The business of less : the role of companies and households on a planet in peril - Geyer, Roland (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The Business of Less rewrites the book on business and the environment. For the last thirty years, corporate sustainability was synonymous with the pursuit of 'eco-efficiency' and 'win-win' opportunities. The notion of 'eco-efficiency' gives us the illusion that we can achieve environmental sustainability without having to question the pursuit of never-ending economic growth. The 'win-win' paradigm is meant to assure us that companies can be protectors of the environment whilst also being profit maximizers. It is abundantly clear that the state of the natural environment has further degraded instead of improved. This book introduces a new paradigm designed to finally reconcile business and the environment. It is called 'net green', which means that in these times of ecological overshoot businesses need to reduce total environmental impact and not just improve the eco-efficiency of their products. The book also introduces and explains the four pollution prevention principles 'again', 'different', 'less', and 'labor, not materials'. Together, 'net green' and the four pollution prevention principles provide a roadmap, for businesses and for every household, to a world in which human prosperity and a healthy environment are no longer at odds. The Business of Less is full of anecdotes and examples. This brings its material to life and makes the book not only very accessible, but also hugely applicable for everyone who is worried about the fate of our planet and is looking for answers"--
Keywords: Industrial management -- Environmental aspects; Business enterprises -- Environmental aspects; Social responsibility of business; Environmental protection; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Environmental Economics